تَاريخُ المَخْطُوطَاتِ وَتَحْقِيقُ التُّرَاثِ وَدَوْرُهُ فِي إِثْرَاءِ الدِّرَاسَاتِ وَالأَبْحَاثِ - صو, خالد (University of Eloued جامعة الوادي, 2020)
يدرسُ البحثُ أهميّةَ المخطوطات وتحقيقها، ودورَها في إثراء الخزينة العلمية، وهو موسوم بـ: "تاريخ المخطوطات وتحقيق التراث ودوره في إثراء الدراسات والأبحاث"، وتهدفُ الدّراسةُ إلى بيان مدى اهتمام الباحثين بالتراث للتعريف بالحضارة العربية والإسلامية من خلال الكنوز التاريخية المخطوطة وتحقيقها، وجاءت هذه الدّراسة في قسمين، أما القسم الأول فيُبيّنُ مدلولَ المخطوطات وما يدلّ عليها، ويعرضُ أهمية تحقيقها ودوافع العناية بها، وأما القسم الثاني فيتناول مفهوم تحقيق المخطوطات، ويعرض مراحلَ اهتمام الباحثين بها، ودورها في إثراء خزانة العلم، ومن أهمّ النتائج التي توصلت إليها الدّراسة أنّ المخطوطاتِ ساهمت بشكل كبير من خلال تحقيقها في استحضار الثقافات القديمة بمبانيها الأصيلة ومعانيها الرّصينة. The research studies the manuscripts’ importance, verification and role in enriching the knowledge treasury, it is entitled: “History of manuscripts and heritage verification and their role in enriching studies and research”, the study aims to show the extent of the researchers ’interest in heritage to introduce the Arab and Islamic civilization through the manuscript historical treasures and their verification, this study came in two sections, the first section explains the meaning of manuscripts and what is indicated by them, it presents the importance of achieving them and the motives for taking care of them, as for the second section, it deals with the concept of verifying manuscripts, it presents the stages of researchers' interest in it and its role in enriching the knowledge treasury, one of the most important findings of the study is that the manuscripts contributed greatly through their achievement of evoking ancient cultures with their original buildings and sober meanings.
قال
Keywords: الكلمات المفتاحية: المخطوطات، التحقيق، المخزون العلميّ، المكتبات. ; Keywords: manuscripts, verification, knowledge treasury, libraries